STUDY ON THE IMPLEMENTATION OF THE BADMINTON GAME IN EXTRACURRICULAR ACTIVITIES AT GRADES V. AND VI. - Cosmin PRODEA; Nicolae JOLDEȘ; Ioan-Nelu POP (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2018)
The paper studies the impact of the implementation of the Badminton game extracurricular activities at secondary school level, and certain aspects relating to the benefits that the game of Badminton brings to the instructive-educational process. Thus, in addition to providing good health, the game of Badminton practiced in an appropriate manner by students at young ages, forms their team and competition spirit, strong characters and feelings of belonging to a community or idea, builds healthy moral values and creates elites. The idea is that Badminton proves to be one of the best ways to achieve the objectives of physical education and sport with regard to the development of the motor qualities of speed and skill. Even more, a constant interest of the students towards the game can be noticed. As a result, the game of Badminton is an alternative to the established sports, with a significant impact on the young generation.